Cytological evaluation of breast lesions with histopathological correlation in patients present with breast lump - Dr. Falguni T. Patel; Dr. Bhoomi A. Shah; Dr. Nisarg R. Parikh; Dr. Ratigar N. Gonsai (Tropical Journal of Pathology and Microbiology, 2019)
Background: Breast carcinoma is the leading cause of death with cancer in women. Management of breast lumps can be challenging in resource poor settings. Fine needle aspiration cytology of breast is an important mode of diagnosis and forms a part of triple assessment, which includes FNAC (fine needle aspiration cytology), mammography and clinical examination. Objective: To examine the cytological details in aspirated smears from lumps in the breast, to evaluate the role of FNAC in improving the quality of diagnosis by comparing with histopathological features and to separate malignant lesions that require more radical therapy from benign ones that may be conservatively managed. Methods: A prospective study is carried out on 100 patients with breast lump over a period of one year including 4 bilateral, 49 left sided and 47 right sided lesions at territory hospital, Chandkheda, Ahmedabad, Gujarat. Histopathology examination were obtained in 27 cases. All the aspirates and histopathology slides were stained with H & E stain. Results: Out of 100 cases of FNAC breast 80 cases were diagnosed as benign and 20 cases were diagnosed as malignant. Histopathological correlation was done on 27 cases and all were confirmed by FNAC. Conclusion: FNAC is a safe, simple, and cost-effective outpatient procedure associated with negligible complication. And along with histopathological correlation it increases the diagnostic accuracy. That helps the clinicians for early diagnosis and specific management thus reducing morbidity and mortality.